Study of morbidity pattern and occupational hazards in sweepers working at a municipal teaching hospital in Mumbai - Palve, Nilesh N.; Shidhaye, Pallavi R.; Chaturvedi, Ramesh M.; Pandit, Daksha D.; Giri, Purushottam A. (International Journal Of Community Medicine And Public Health, 2017)
Background: The International Labour Organization (ILO) estimates that more than 125 million workers are victims of occupational accidents and diseases in a single year. The important morbid conditions detected in the workers include the diseases of the respiratory system and eye, accidents, injuries, cuts and wounds, skin infections, animal bites, etc. Health Care Workers (HCWs) are attributed to the group at highest risk of occupationally acquired blood borne diseases as the result of contact with blood and body fluids. The present study was conducted to assess the morbidity pattern and occupational hazards in the sweepers working at the tertiary care teaching hospital in Mumbai. Methods: A cross-sectional epidemiological study was carried out in the various wards of Lokmanya Tilak municipal medical college & general hospital, Mumbai during the period of January 2008 to May 2009. Total 267 sweepers were interviewed. A pre-designed and pre-tested questionnaire was used to get information regarding the morbidity pattern and occupational hazards in the sweepers. Results: Out of 267, history of acute illness was elicited from 64 (23.97%) employees. 52 (19.47%) sweepers had history of chronic illness. Among the sweepers, 160 (59.9%) had some sort of morbidity present. The morbid conditions found in the sweepers were musculoskeletal disorders 55 (20.6%), hypertension 46 (17.2%), gastrointestinal problem 26 (9.7%), eye disorders 23 (8.6%) and respiratory system diseases 21 (7.9%). The present study showed that, 226 (84.6%) sweepers used some form of personal protective devices regularly and 41 (15.4%) didn’t use regularly. 113 (42.3%) sweepers had needle prick or sharp injury. 74 (65.5%) sweepers had single needle prick or sharp injury & 39 (34.5%) sweepers had repeated needle prick or sharp injury. Conclusions: Periodic examination should be done annually & immediate corrective measures should be taken to protect the health of employees at risk. Stress management principles must be implemented in the sweepers to enhance physical and mental health. There is need for safety training programme for all health workers including sweepers in the hospitals.